Study of periostin levels in patients before and after acute myocardial infarction - Thang, Doan Chi; Nguyen, Tran Khoi; Tin, Nguyen Trung; Minh, Huynh Van; Tien, Hoang Anh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: There is a clear correlation between inflammatory outcome signs and adverse outcomes in patients after acute myocardial infarction. Periostin - an inflammatory biomarker in recent times promises to be an effective and necessary factor in predicting disease progression. This study described characteristics of serum periostin levels in patients with acute MI and some follow up results of this biomaker. Methods: Study design: Analytical cross-sectional study. Non-probability, purposive sampling. The research subjects were divided into 2 groups: the group of patients diagnosed with acute MI (including 153 patients) and the remaining group was the control group (including 153 healthy people) . All patient groups and the control group were hospitalized and treated from September 2019 to March 2023. Results: There was no difference in age, BMI and sex between the patient group and the control group (p < 0.05). The serum periostin level in acute MI patients was the highest (149.37ng/ml, IQR: 120.69 - 208.18), then the level at 3 months post-MI (77.69 ng/ml, IQR: 61.63 - 101.05), the control group’s periostin level was the lowest (63.04 ng/ml, IQR: 40.96 - 80.98), the difference was statistically significant (p < 0.05). Median periostin level in Killip I group (132.28 ng/ml) was lower than in the remaining group (187.84 ng/ml) (p < 0.05). Mean serum periostin level in the LVEF < 50% group (208.15 ± 92.33 ng/ml) was significantly greater than that in the LVEF ≥ 50% group (136.92 ± 38.68 ng/ml), (p < 0.05). Conclusion: Serum periostin levels increase in acute myocardial infarction and decrease gradually post myocardial infarction. There is a difference in admission periostin levels between preserved and reduced EF groups.